Risk for cervical intraepithelial neoplasia grade 2 or higher (CIN2+) among women with histologically confirmed CIN1 or less in cervical cancer screening - Tverelv, Liv Reidun (UiT Norges arktiske universitet, 2017)
Background/objective: Follow-up after histologically confirmed normal/CIN1 in cervical cancer screening is less studied. The current Norwegian follow-up guideline is combined cytology and HPV-testing after six months. The study objective is to examine compliance to guidelines and subsequent risk for CIN2+ in this subset of women. Materials and methods: Women aged 25-69 years in Troms and Finnmark counties attending the Norwegian Cervical Cancer Screening Programme were included in this registry-based cohort study. An exposed cohort with histologically confirmed normal/CIN1 after ASC-US/LSIL or ASC-H/HSIL cytologies (N=374) was compared to a control cohort having normal cytologies in primary screening (N=25,948). The exposed cohort was stratified by the first follow-up cytology being normal or abnormal. Both cohorts were followed up to the last time-point of observation of 78 months. Results: 69.5% of the exposed cohort and 42.2% of the control cohort was compliant to guidelines. The 42-month cumulative incidence of CIN2+ was, in the exposed cohort 17.9% (abnormal follow-up) and 7.1% (normal follow-up), and 0.43% in the control cohort (p < 0.01). The 42-month cumulative incidence of CIN3+ was 2.5% (95% CI: 0.0-5.2) in the exposed cohort with normal follow-up. Age-adjusted HR for CIN2+ was 22.5 (abnormal follow-up) and 9.0 (normal follow-up) (p < 0.01). Women aged 25-39 years had higher CIN2+ risks compared to women aged 55-69 years (HR 6.1, p < 0.01). Conclusion: Compliance to guidelines was better, and the cumulative incidence of CIN2+ was significantly higher among women attending follow-up after histologically confirmed normal/CIN1 compared to women having normal cytologies in primary screening. The CIN2+ risk was higher among younger women. The cumulative incidence of CIN3+ provided by a normal follow-up cytology after histologically confirmed normal/CIN1, was closely consistent to allow screening in three years. A negative co-test probably provides a risk consistent to safe return to screening ...